Susceptibility of kiwifruit (Actinidia spp.) cultivars to Ceratitis capitata (Diptera: Tephritidae) infestation. (22nd February 2013) - Papachristos, D. P.; Papadopoulos, N. T.; Maglaras, E.; Michaelakis, A.; Antonatos, S. Α.
Abstract Laboratory no‐choice tests were conducted to determine whether the kiwifruit cultivars Hayward, Tsechelidis (Actinidia deliciosa) and Soreli (A. chinensis) are hosts of the Mediterranean fruit fly, Ceratitis capitata. Kiwifruits were exposed to gravid females for 24 h, and the number of eggs laid as well as larval developmental rates and survival rates of immatures' was determined. Moreover, oviposition and survival rates were recorded for adults obtained from the above three cultivars. Similar experimental procedures were followed using nectarines (Prunus persica), a favourable host for C. capitata. Furthermore, using McPhail‐type traps loaded with food attractants, we compared adult population densities in four kiwifruits and adjacent citrus orchards. Infestation rates were also determined in kiwifruits collected from the above kiwifruit orchards. The results demonstrate that C. capitata, under laboratory conditions, oviposit on all three kiwifruit cultivars tested. The numbers of eggs laid and survival rates of immatures were significantly lower for the two cultivars of A. deliciosa compared with nectarines. On the other hand, oviposition rates were much higher in the cultivar Soreli (A. chinensis) compared with nectarines; however, none of the immatures reached adulthood. Adults obtained from the Hayward and Tsechelidis cultivars had shorter longevity and females were less fecund than those obtained from nectarines. Adult Mediterranean fruit flies were captured in all four kiwifruit orchards, but at significantly lower numbers compared with citrus orchards. Fruit sampling from the Hayward and Tsechelidis cultivars indicated a minimal infestation of the Hayward fruits only (0.41%), which, however, resulted in no adult emergence. Removal of the fruit surface hairs of Hayward cultivar increased dramatically the oviposition rates of C. capitata in laboratory conditions, suggesting significant oviposition‐deterrent properties. The importance of our findings for determining a non‐host status for kiwifruits is discussed.